Pengaruh Etika Komunikasi Organisasi terhadap Kenyamanan Anggota dalam Organisasi Mahasiswa Manajemen Universitas Muhammadiyah Bandung - Ghulam Priyatna Yoniar; Susi Nurohimah; Alma Aulia Siffa; Amira Muthi Ghassani; Sofa Parihah Nurasiah (Indo Publishing, 2026)
Organizational communication ethics play an important role in creating a comfortable and supportive organizational environment for its members. Communication based on mutual respect, openness, honesty, and responsibility is believed to enhance members' comfort and engagement within the organization. This study aims to analyze the effect of organizational communication ethics on members' comfort in the Student Organization of the Management Study Program at Universitas Muhammadiyah Bandung. This research employed a quantitative approach using a survey method. The study involved 35 respondents selected through purposive sampling. Data were collected using a Likert-scale questionnaire and analyzed through descriptive analysis and simple linear regression. The results indicate that organizational communication ethics have a positive and significant effect on members' comfort. Descriptive analysis also reveals that both organizational communication ethics and members' comfort are categorized as high. These findings suggest that better implementation of ethical communication within the organization contributes to higher levels of members' comfort. Therefore, student organizations are encouraged to strengthen ethical, open, and respectful communication practices to create a more conducive organizational environment and improve members' active participation.